Christianity in a revolutionary age ; v. 4 a history of Christianity in the nineteenth and twentieth centuries - Latourette, Kenneth Scott 1884-1968 (Exeter, UK Paternoster, 1970)
Contents : v. 4 : The twentieth century in Europe : the Roman Catholic, Protestant and Eastern churches. Includes bibliographical references and index.
First edition published 1958, New York, Harper and Row.
Keywords: Church history -- 20th century